PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL COOPERATIVETIPENUMBERED HEAD TOGETHER DI SEKOLAH DASAR - Nurulita, Risa; Sugiyono, Sugiyono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to improve student learning outcomes using the Numbered Heads Together type cooperative model in the learning of Social Sciences in class V SDS Islamiyah Southeast Pontianak. This research uses descriptive method with class action research (CAR) and is collaborative. Data collection techniques used are direct observation and measurement. The data analysis technique used is to use an average calculation formula. This study was carried out in 3 cycles with results 1) the average ability of the teacher to plan learning, namely as follows, in the first cycle of 3.17, in the second cycle was 3.26, in the third cycle was 3.50. 2) the average ability of teachers to carry out learning as follows, in the first cycle of 3.13, in the second cycle of 3.19, in the third cycle of 3.50. 3) the average student learning outcomes are as follows, in cycle I is 66.66, in cycle II is 73.41, and in cycle III is 82.53. From the data obtained, it can be concluded that the Numbered Heads Together type cooperative model can improve student learning outcomes.Keywords: Improvement, learning outcomes, Numbered Heads Together type cooperative model. Social Sciences